Translation of culture-loaded words in Hong Lou Meng based on eco-translatology theory - Lim, Min Li; Husin, Norhazlina; Lee, Ai Chat (Universiti Teknologi MARA, 2024)
The research is aimed to explore the reasons leading to the different translation of culture-loaded words and their transformation levels in the Chinese classic novel Hong Lou Meng. The qualitative method was adopted in the re-search. Guided by eco-translatology, the study compares the translation of culture-loaded words in the two English versions of Hong Lou Meng by David Hawkes and Yang Hsien-Yi from the three micro aspects of eco-translatology theory: language dimension, culture dimension and communication dimension. Based on the comparison, the reasons resulting in the differences will be explored from three perspectives of the translation ecosystem to reasonably explain the differences between the two translations. The findings show that both Hawkes and Yang tried to adapt to the eco-system of the target language by adopting different methods. Hawkes managed to balance conveying the surface and implied meaning of the culture-loaded words in the source text and the readiness and acceptability of the target read-ers. Yang tended to spread Chinese culture to the target readers. The two translations have managed to adapt to the source and target ecosystems and achieved different levels of ecological transformation in the three dimensions. The three factors of the source text, the translation purpose and the press can well explain the differences between the two translations and provide a fair evaluation. It also shows the great explanatory power of eco-translatology. The study also shows the explanatory power of eco-translatology in the field of translation studies.